Application of static synchronous compensator and energy storage system for power system stability enhancement - Mohammed Salheen Alatshan; Ibrahim Alhamrouni; Tole Sutikno; Awang Jusoh (Bulletin of Electrical Engineering and Informatics, 2020)
The major drivers of the quest for optimal placement of flexible alternating current transmission system (FACTS) devices are the quest for smart grids and economic indicators. The demand for energy and power stability will continue much as the astronomic growth in industries and increase in global population remains. The aim of this paper is to deliver a panoramic view of the use of static synchronous compensator (STATCOM) in combination with energy storage system (ESS) in order to enhance power stability. In this paper, it was observed that application of ESS is an important factor in attaining power stability and mitigating the effect of dynamics associated with the power supply system. The miniaturization of batteries and adequate placement of STATCOMs will be a challenge much as new power system are built or existing ones are expanded. The future of ESS is towards the adoption of renewable energy sources as against batteries.